2014
DOI: 10.1002/app.40833
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of polyamidoxime chelating ligand from polymer‐grafted corn‐cob cellulose for metal extraction

Abstract: A conventional free-radical initiating process was used to prepare graft copolymers from acrylonitrile (AN) with corn-cob cellulose with ceric ammonium nitrate (CAN) as an initiator. The optimum grafting was achieved with corn-cob cellulose (anhydroglucose unit, AGU), mineral acid (H 2 SO 4 ), CAN, and AN at concentrations of 0.133, 0.081, 0.0145, and 1.056 mol/L, respectively. Furthermore, the nitrile functional groups of the grafted copolymers were converted to amidoxime ligands with hydroxylamine under basi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 27 publications
2
37
0
Order By: Relevance
“…17,19,37,38 In this study, cotton cellulose was graed with EMCA via a free-radical initiation method, which involved CAN as an initiator (Fig. 1b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…17,19,37,38 In this study, cotton cellulose was graed with EMCA via a free-radical initiation method, which involved CAN as an initiator (Fig. 1b).…”
Section: Resultsmentioning
confidence: 99%
“…17,[21][22][23] Furthermore, amidoximated cellulose can act as a nanoreactor to produce nanocomposites with tailored characteristics. 24,25 Also, amidoxime-reduced metal nanocomposites possess potent antimicrobial functionality.…”
Section: Polymeric Ligands Bearing Amidoxime (R-c(nh 2 )]N-oh) or Hydmentioning
confidence: 99%
“…The trend in the curve showed that the adsorption of the metal ions increased with increasing pH. Thus, the synthesized Khaya cellulosebased poly(amidoxime) ligand functioned as an adsorbent, forming complexes with the metal ions that prompted their subsequent removal from wastewater (Lutfor et al 2001;Yong et al 2012;Awual et al 2013;Lutfor et al 2014).…”
Section: Effect Of Ph On the Removal Of Various Transition Metal Ionsmentioning
confidence: 99%
“…The termination reaction of the growing polymer chain of the cellulose-monomer results in the combination of grafting (Fig. 4) (Lutfor et al 2014). …”
Section: Graft Copolymerizationmentioning
confidence: 99%
See 1 more Smart Citation